Biochemical compounds and pharmacological functions of a traditional Chinese medicinal herb Polygonati rhizoma - Guoqun Yang; Dong Jiang; Bo Chen; Jianhua Huang; Li-Jun Huang; Ning Li (Medicinal Plant Biology)
Polygonati rhizoma (Huangjing in China) is a widely utilized medicinal and edible plant within traditional Chinese medicine, displaying significant potential for medicinal application, agricultural value, and societal importance. Enriched with polysaccharides, saponins, flavonoids, alkaloids, and other bioactive ingredients, it serves as both a nutrient-dense supplementary food and an alternative therapeutic agent for prevention. Although Polygonati rhizoma's purported anti-aging, anti-tumor, anti-diabetic, and physiological regulatory properties have been postulated, the specific ingredients and underlying mechanisms remain largely elusive. Due to its notable bioactive effects on human health, Polygonati rhizoma has garnered considerable attention and has undergone extensive research. In recent years, modern research with multidimensional approaches has achieved an understanding of the biochemical nature and pharmacological mechanism of Polygonati rhizoma. It is anticipated that Polygonati rhizoma holds the potential to emerge as a pivotal resource for the development of novel pharmaceuticals and therapeutic strategies targeting various human ailments. This review synthesizes the latest research on Polygonati rhizoma, centering on its effects related to anti-aging, anti-tumor, anti-diabetic, and physiological regulation aspects. Furthermore, we evaluate the specific mechanisms through diverse perspectives and provide insights into often overlooked facets of Polygonati rhizoma's pharmacological potential, aiming to contribute valuable suggestions that could advance its incorporation and practical utilization within the framework of modernized traditional Chinese medicine.